Pengaruh Servant Leadership, Motivasi, dan Komitmen terhadap Kinerja Majelis Jemaat Gki Kota Wisata - Roestandi, David; Winarto, Jacinta (SAFE-Network, 2025)
This study aims to analyze the influence of servant leadership, motivation, and commitment on the performance of the GKI Kota Wisata Church Council. A quantitative approach was employed through a survey of 30 respondents comprising elders and pastors. Data were collected using a Likert-scale questionnaire and analyzed using the Structural Equation Model-Partial Least Square (SEM-PLS) method. This study seeks to provide insights into the importance of implementing servant leadership, work motivation, and organizational commitment to enhance the effectiveness of church services. The findings of this study indicate that servant leadership, motivation, and commitment significantly influence the performance of the Church Council at GKI Kota Wisata.